Pengaruh Struktur dan Mekanisme Corporate Governance Terhadap Tingkat Kepatuhan Mandatory Disclosure (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di BEI yang Tergabung pada LQ45 Periode 2011-2015) - Nanda, Satriavi Mega, Dr. Erma Setiawati, Ak, MM (2017)
The purpose of this study was to determine the level of mandatory disclosure to determine the effect of structure and mechanism corporate governance that identified as managerial ownership, institusional ownership, the number of audit committee, the number of audit committee meetings, the proportion of independent commissioner and the number of meeting of the board of commissioner. This research uses a sample of manufacturing companies that are listed in the Indonesia Stock Exchange registered of Indeks LQ45 from the 2011-2015 research period. The sample is chosen using a purposive sampling method, and 141 companies are used for the sample. Data analysis with classic assumption and hypothesis test is used multiple regression method in SPSS 21.0 software. The result of multiple regression showed that corporate governance structure and mechanism affects the level of mandatory disclosure. Independent variables that affect the level of mandatory disclosure are managerial ownership, number of audit committee meetings and number of meeting of the board of commissioner. Other variable namely are institusional ownership, the number of audit committee and the proportion of independent commissioner do not affect the level of mandatory disclosure. Keywords: managerial ownership, institutional ownership, audit committee number, audit committee meeting number, independent commissioner proportion, and commissioner board meeting number, mandatory disclosure compliance level.